2016
DOI: 10.1016/j.synthmet.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Blue photoluminescence N-substituted poly(4H-benzo[def]carbazole)s

Abstract: N-Alkyl and N-phenyl substituted poly(carbazole)s having a 4,5-ethenylene bridge, poly(4H-benzo[def]carbazole)s, were newly synthesized. Poly(carbazole)s having a 4,5-ethylene bridge were also synthesized for comparison. They were prepared from corresponding dibromo monomers by Ni(0)-catalyzed Yamamoto polycondensation. All the polymers had good solubility in common organic solvents, enough high molecular weights to make thin films, and good thermal stability showing about 400 °C of temperature at 5 wt% loss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For recent background literature on the chemistry of related carbazole-derived compounds and their applications, including syntheses of bioactive carbazoles, see: (Chakraborty et al, 1965;Bondock et al, 2019) and references cited therein. The syntheses of related benzo[def]carbazoles are described by Pocock et al (2021) and Geng et al (2016). For applications of benzo [def]carbazole derivatives, see: Vespa et al (2018), Atakan & Gunbas (2016) and Mys ´liwiec et al (2015).…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For recent background literature on the chemistry of related carbazole-derived compounds and their applications, including syntheses of bioactive carbazoles, see: (Chakraborty et al, 1965;Bondock et al, 2019) and references cited therein. The syntheses of related benzo[def]carbazoles are described by Pocock et al (2021) and Geng et al (2016). For applications of benzo [def]carbazole derivatives, see: Vespa et al (2018), Atakan & Gunbas (2016) and Mys ´liwiec et al (2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The effect of the solvent on absorption and fluorescence bands as well as comparisons with theoretical expectations have been used to estimate the dipole moment of the first excited state. Geng et al (2016) reported the optimized geometry, electron-density distributions, and HOMO and LUMO of carbazole and 4H-benzo[def]carbazole. Changes in the HOMO-LUMO gap (Eg) and the design of molecules for material applications can be realized by comparing frontier molecular orbitals, HOMO and LUMO energy levels, and exploring their electron-density maps.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Recently, an approach for the synthesis of 4 H ‐benzo[ def ]carbazole starting from 4‐iodophenanthrene and diaziridinone through C‐H activation and amination has been developed (Scheme 1f) [32]. Kijima et al reported a synthetic strategy, including nitration, reductive ring closure, and dehydrogenation in sequence, to provide benzo[ def ]carbazole (Scheme 1g) from 9,10‐dihydrophenanthrene [33]. Very recently, a direct formation of 4,5‐disubstituted carbazoles through the use of n BuLi–TMEDA for lithiation and annulation with hexafluorobenzene gave the structure of 4 H ‐naphtho[1,2,3,4‐ def ]carbazole (Scheme 1h) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the solvent effects on absorption and fluorescence bands as well as comparison with theoretical expectations have been used to estimate the dipole moment of the first excited state. In 2016, Geng et al reported the optimized geometry, electron density distributions, and HOMO and LUMO of carbazole and 4 H ‐benzo[ def ]carbazole [33]. One can realize the changes of HOMO‐LUMO gap ( Eg ) and design molecules for material applications by comparing frontier molecular orbitals, HOMO and LUMO energy levels, and exploring their electron density maps.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the energy efficiency, polymer light‐emitting diodes (PLEDs) are promising devices that can exhibit acceptable light‐emitting efficiencies and lower electrical consumption than conventional light sources, such as incandescent and fluorescent lamps . Concerning the eco‐friendly and alternative energy production, polymer photovoltaic cells (PSCs) are promising tools to convert directly the absorbed solar radiation into electrical energy, due to their flexibility and straightforward scale‐up production.…”
Section: Introductionmentioning
confidence: 99%